Governance mechanism and intellectual capital on financial performance in banking industries - Nungky Ruslandy; Lia Uzliawati; Nurhayati Sholeha (Jurnal Mantik, 2023)
Banking in the current technological era must be able to compete with other banks by innovating through its resources so as to attract consumer interest. Intellectual capital is an intangible asset owned by a company that can have added value to financial performance. This study aims to examine Intellectual Capital as a moderator of Mechanism Governance proxied by Independent Commissioners and the Board of Directors on Financial Performance proxied by ROA. The sample used in this study is the banking annual report listed on the IDX for 2019-2021. Moderating Regression Analysis is used as an analytical tool in this study. The results of the study show that the Independent Commissioner has a non-significant positive influence on ROA. The Board of Directors has a significant negative influence on ROA. Meanwhile, the influence of the Independent Commissioners and the Board of Directors on ROA can be moderated by Intellectual Capital . The Existence of independent commissioners and boards of directors can improve management performance to be able to focus more on intellectual capital in the company